(untitled) (International Journal of Environmental Sciences, 2025)
The study was conducted under the conditions of Nineveh Governorate - Iraq on the nature of inheritance of some growth and yield traits of two imported potato varieties of the E rank (Bada and Sefra) under the influence of three types of covering treatments (exposed (without covering), green plastic covering and transparent plastic covering), during the spring growing season of 2024/2025 at the College of Agriculture and Forestry / University of Mosul as a factorial experiment with six treatments according to the complete randomized block design and three replicates.The results of the analysis of variance indicate that there were significant differences between the two cultivars for all studied traits except the number of aerial stems. The Bada cultivar had a significant superiority over the Sefra cultivar, as well as the treatments of green and transparent plastic covering over the open for the yield traits represented by the total plant yield, total tuber yield, marketable plant yield, and marketable tuber yield. The Bada cultivar plants covered with green plastic gave the best values ​​for the total plant yield and total tuber yield, while the Sefra cultivar plants covered with transparent plastic gave the best values ​​for the marketable plant yield and marketable tuber yield.Genetic and environmental variances were significant for all traits. Broad-sense heritability was high for plant height, total number of tubers per plant, number of marketable tubers per plant and total tuber weight. The high heritability indicates that the appearance of the individual is closely related to its genetic makeup, which suggests the possibility of introducing direct improvements to these traits in the following seasons. The expected genetic improvement values ​​as a percentage of mean were moderate for most of the studied traits.